Role of Integrins in the Assembly and Function of Hensin in Intercalated Cells - Vijayakumar, Soundarapandian (American Society of Nephrology, 2008)
Epithelial differentiation proceeds in at least two steps: Conversion of a nonepithelial cell into an epithelial sheet followed by terminal differentiation into the mature epithelial phenotype. It was recently discovered that the extracellular matrix (ECM) protein hensin is able to convert a renal intercalated cell line from a flat, squamous shape into a cuboidal or columnar epithelium. Global knockout of hensin in mice results in embryonic lethality at the time that the first columnar cells appear. Here, antibodies that either activate or block integrin β1 were used to demonstrate that activation of integrin αvβ1 causes deposition of hensin in the ECM. Once hensin polymerizes and deposits into the ECM, it binds to integrin α6 and mediates the conversion of epithelial cells to a cuboidal phenotype capable of apical endocytosis; therefore, multiple integrins play a role in the terminal differentiation of the intercalated cell: αvβ1 generates polymerized hensin, and another set of integrins (containing α6) mediates signals between hensin and the interior of the cells.